Electrochemical Biosensor Based on Horseradish Peroxidase and Black Phosphorene Quantum Dot Modified Electrode - Xiaoqing Li; Fan Shi; Lisi Wang; Siyue Zhang; Lijun Yan; Xiaoping Zhang; Wei Sun (Molecules, 2023)
Black phosphorene quantum dots (BPQDs) were prepared by ultrasonic-assisted liquid-phase exfoliation and centrifugation with morphologies proved by TEM results. Furthermore, an electrochemical enzyme sensor was prepared by co-modification of BPQDs with horseradish peroxidase (HRP) on the surface of a carbon ionic liquid electrode (CILE) for the first time. The direct electrochemical behavior of HRP was studied with a pair of well-shaped voltammetric peaks that appeared, indicating that the existence of BPQDs was beneficial to accelerate the electron transfer rate between HRP and the electrode surface. This was due to the excellent properties of BPQDs, such as small particle size, high interfacial reaction activity, fast conductivity, and good biocompatibility. The presence of BPQDs on the electrode surface provided a fast channel for direct electron transfer of HRP. Therefore, the constructed electrochemical HRP biosensor was firstly used to investigate the electrocatalytic behavior of trichloroacetic acid (TCA) and potassium bromate (KBrO3), and the wide linear detection ranges of TCA and KBrO3 were 4.0–600.0 mmol/L and 2.0–57.0 mmol/L, respectively. The modified electrode was applied to the actual samples detection with satisfactory results.